2012
DOI: 10.1242/jcs.093104
|View full text |Cite
|
Sign up to set email alerts
|

Orientation-based FRET sensor for real-time imaging of cellular forces

Abstract: SummaryMechanical stress is an unmapped source of free energy in cells. Mapping the stress fields in a heterogeneous time-dependent environment like that found in cells requires probes that are specific for different proteins and respond to biologically relevant forces with minimal disturbance to the host system. To meet these goals, we have designed a genetically encoded stress sensor with minimal volume and high sensitivity and dynamic range. The new FRET-based sensor, called cpstFRET, is designed to be modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
128
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(132 citation statements)
references
References 25 publications
4
128
0
Order By: Relevance
“…Because the stress-fiber geometry should be relatively easy to estimate for cells on 2D substrate, these can simplify to one angle and one tension measurement. A number of strategies may be possible for the design of a single-molecule talin geometry reporter, such as a geometry-dependent FRET sensor (59) or by single-molecule localization of a pair of spectrally distinct FPs incorporated at welldefined sites within talin. Direct and simultaneous measurements of force and force-transmission structures in living cells will be instrumental in understanding how complex mechanosensitive responses originate in FAs.…”
Section: Discussionmentioning
confidence: 99%
“…Because the stress-fiber geometry should be relatively easy to estimate for cells on 2D substrate, these can simplify to one angle and one tension measurement. A number of strategies may be possible for the design of a single-molecule talin geometry reporter, such as a geometry-dependent FRET sensor (59) or by single-molecule localization of a pair of spectrally distinct FPs incorporated at welldefined sites within talin. Direct and simultaneous measurements of force and force-transmission structures in living cells will be instrumental in understanding how complex mechanosensitive responses originate in FAs.…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows many macroscopic effects of mechanical stress on cellular processes including cell motility, embryogenesis, stem cell replication and differentiation (3,4), bone and muscle homeostasis, gene expression, protein folding (5), and membrane potential (6). However, these studies lacked the ability to measure stress in specific structural proteins, and the analyses have tended to treat cytoskeletal stresses as uniform, which we now know is not true (2,7). We, and other groups (8), have shown that the distribution of forces is nonuniform in both time and space and protein specificity (9).…”
mentioning
confidence: 99%
“…We have used a variety of different linkers and some that match the compliance of the host protein (7,11,12). All of the published work on force probes has required a host protein that is linear, so the probes can be coded into the DNA of the host protein.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is, therefore, a persistent need for methods to apply and modulate mechanical forces inside living tissues. Methods to measure forces by fluorescence resonance energy transfer-based mechanosensors in living cells are becoming available (Meng and Sachs 2012), and these will also be extremely important for learning more about the relation of mechanics to ciliogenesis.…”
Section: Future Challengesmentioning
confidence: 99%